Antibacterial Activity and Mechanism of Action of Aspidinol Against Multi-Drug-Resistant Methicillin-Resistant Staphylococcus aureus - Hua, Xin; Yang, Qin; Zhang, Wanjiang; Dong, Zhimin; Yu, Shenye; Schwarz, Stefan; Liu, Siguo (Frontiers in Pharmacology, 2018)
This study aimed at investigating the antibacterial activity of aspidinol, an extract from Dryopteris fragrans (L.) Schott, against methicillin-resistant Staphylococcus aureus (MRSA). MRSA isolates were treated with aspidinol to determine the differential expression of genes and associated pathways following the drug treatment. Aspidinol displayed significant anti-MRSA activity, both in vivo (MIC = 2 μg/mL) and in vitro, and achievedreached an antibacterial effect comparable to that of vancomycin. In the lethal septicemic mouse study, a dose of 50 mg/kg of either aspidinol or vancomycin provided a significant protection from mortality. In the non-lethal septicemic mouse study, aspidinol and vancomycin produced a significant reduction in mean bacterial load in murine organs, including the spleen, lung and liver. After treatment with aspidinol, we found through RNA-seq and RT-PCR experiments that the inhibition of the formation of ribosomes was the primary S. aureus cell-killing mechanism, and the inhibition of amino acid synthesis and the reduction of the virulence factors might play a secondary role.